Relationships between asymmetries in functional movements and the Star Excursion Balance Test - Overmoyer, Grant, author; Reiser, Raoul, II, advisor; Browning, Ray, committee member; Gilkey, David, committee member (Colorado State University. Libraries, 2012)
Lower extremity functional asymmetries (LEFA) as well as the Star Excursion Balance Test (SEBT) have been used to screen for injury risk and assess post-injury function. Both have also been shown to relate to physical performance. However, the relationships between LEFA, observed during different tasks, are not well understood, nor are the relationships between LEFA and side-to-side asymmetries in SEBT scores. As a result, it is difficult to determine which methods are most appropriate to assess detrimental asymmetries and whether they might be interchangeable. PURPOSE: The goal of this investigation was to examine the correlation in LEFA using measurement of vertical ground reaction forces (GRFv) during quiet standing, body weight squats, maximal effort counter-movement jumps (CMJ) and single-leg drop landings from a 30.5 cm platform (SLDL). Another goal was to investigate bilateral asymmetries in the SEBT anterior (Ant), posteromedial (PostMed) and posterolateral (PostLat) excursion directions, in both the correlations to each other and the correlations to the four functional movement tasks listed above. METHODS: Twenty recreationally active men (n=9) and women (n=11) (mean ± SD age: 21.9 ± 2.6 yrs; height 171 ± 8.8 cm; mass 67.2 ± 1.9 kg) performed three measured trials of each excursion direction of the SEBT, five 20 second quiet standing trials, five unloaded (body weight) squats, five CMJ and five SLDL on each side. Leg length measurements, GRFv data and SEBT scores for each leg were collected. Asymmetry was calculated by subtracting the % load on the preferred kicking leg (KL), or during the SEBT the percent of the bilaterally summed score on the KL, from that of the non-preferred kicking leg (NKL). Results were analyzed using Pearson's correlation and paired t-tests. Eleven subjects were reassessed for repeatability measures. RESULTS: Significant correlations (p<0.05) were found between asymmetries in several of the parameters measured in the LEFA tasks. Standing and average GRFv during CMJ significantly correlated to each other (r= 0.458); average GRFv during squats significantly correlated with standing GRFv (r= -0.452); both maximum and average GRFv during the squat significantly correlated with average and maximum GRFv during CMJ (r= -0.571 to -0.768). Average GRFv to peak in the SLDL significantly related to the squat (r= -0.494 to -0.500) and peak GRFv during the SLDL significantly related to CMJ average GRFv (r= -0.470). Further significance was identified among asymmetries in several SEBT excursion directions, particularly between the Ant versus PostMed (r= 0.406 to 0.564), and Ant versus PostLat (r= 0.470 to 0.570). There was a wide range of significant correlations in regards to combinations of these scores in the SEBT (r= 0.470 to 0.973). And finally, correlations were found to exist between several of the LEFA tasks and SEBT excursion directions. These included squats versus PostMed and Ant (r= 0.489 to 0.593 and r= 0.315 to 0.514, respectively), CMJ versus all excursion directions (r= -0.379 to -0.649) and the SLDL slope to peak, average GRFv to peak and average GRFv to 300ms, versus Ant (r= -0.402 to -0.609). LEFA tasks and SEBT asymmetries were generally found to be highly repeatability (α= 0.758 to 0.992 and α= 0.752 to 0.976, respectively), but with generally much lower and a wider range of repeatability shown in the absolute measures of asymmetry (LEFA: α= 0.212 to 0.791 and SEBT: α= 0.133 to 0.802). CONCLUSION: While most measures were highly repeatable, because the correlations between tests were of only mild to moderate strength, it is unlikely that any one test studied here could be used to accurately predict performance on any of the other tests, at least in a relatively healthy young population. Therefore, multiple tests may be necessary with specific attention on those that most closely replicate the movement patterns and specific performance needs of the individual.
Keywords: assessment; asymmetry; balance; ground reaction force; movement screening; star excursion balance test